Association between the time of day at stroke onset and functional outcome of acute ischemic stroke patients treated with endovascular therapy. Issue 12 (December 2022) - Wang, Xian; Wang, Xiaoyin; Ma, Jin; Jia, Milan; Wu, Longfei; Li, Weili; Li, Chuanhui; Wu, Chuanjie; Ren, Changhong; Chen, Xin; Zhao, Wenbo; Ji, Xunming
To investigate the association between time-of-day of stroke onset and functional outcome in patients with acute ischemic stroke(AIS) treated with endovascular thrombectomy(EVT). AIS patients treated with EVT between January 2013 and December 2018 were recruited and divided them into four 6-h interval groups according to the time-of-day of stroke onset. A total of 438 patients were enrolled, 3-month favorable outcome were achieved in 58.6%, 43.7%, 36.6%, and 30.5% of patients in the 00:00–06:00, 06:00–12:00, 12:00–18:00, and 18:00–24:00 groups, respectively (adjusted OR 0.61, 95% CI 0.40–0.93; p  = 0.020). Compared with the 18:00–24:00 interval, patients in the 00:00–06:00 interval (adjusted OR 4.01, 95%CI 1.02–15.80, p  = 0.047) and the 06:00–12:00 interval (adjusted OR 3.24, 95% CI 1.09–9.64, p  = 0.034) were more likely to achieve favorable outcome. The time-of-day of stroke onset was not associated with 3-month mortality (adjusted p = 0.829), symptomatic intracerebral hemorrhage (sICH, adjusted p  = 0.296), or early successful recanalization (adjusted p  = 0.074). In conclusion, in AIS patients treated with EVT, those onsets either between 00:00 and 06:00 or between 06:00 and 12:00 appeared to be associated with a higher proportion of favorable outcomes at 3 months, but the time-of-day at stroke onset was not associated with the incidence of sICH, rate of early successful recanalization, or 3-month mortality.